2016
DOI: 10.1002/cctc.201600657
|View full text |Cite
|
Sign up to set email alerts
|

3 D Imaging and Structural Analysis of a Mesoporous‐Silica‐Body‐Supported Eggshell Cobalt Catalyst for Fischer–Tropsch Synthesis

Abstract: For understanding the relationship between the structure and catalytic property and further optimizing the synthetic steps, it is imperative to obtain basic information about the characteristics of heterogeneous catalysts, such as porosity, dispersion, and accessibility of the active metal phases. Herein, we reported a multiscale analysis of an eggshell‐Co‐based catalyst for the Fischer–Tropsch synthesis (FTS), which was prepared by wetness impregnation. Conventional characterization techniques, such as mercur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…The syngas so synthetized could be used to produce synthetic petroleum via the Fischer-Tropsch process. Precisely, Han et al (2016) have recently reported a multiscale analysis of an eggshell-Co-based catalyst prepared by wetness impregnation for this synthesis.…”
Section: Synthesis Of Hydrogen/syngasmentioning
confidence: 99%
“…The syngas so synthetized could be used to produce synthetic petroleum via the Fischer-Tropsch process. Precisely, Han et al (2016) have recently reported a multiscale analysis of an eggshell-Co-based catalyst prepared by wetness impregnation for this synthesis.…”
Section: Synthesis Of Hydrogen/syngasmentioning
confidence: 99%